Interactive effect with AM fungi and Azotobacter inoculated seed on germination, plant growth and yield in cotton (Gossypium hirsutum) - PAUL, SANGEETA; RATHI, MAHESHWAR SINGH; TYAGI, SATYA PRAKASH (The Indian Journal of Agricultural Sciences, 2011)
Studies were carried out to evaluate the response of cotton to inoculation with IAA producing diazotroph, Azotobacter chroococcum. The effect of A. chroococcum inoculation on cotton seed germination and seedling development was observed to be beneficial for both parameters. A field experiment was also conducted to ascertain the effects of dual inoculation of A. chroococcum (CBD-15, M-4, BA-l and OA-4) as seed application and AM fungi as soil inoculant on cotton (Gossypium hirsutum L.) var. Pusa 8-6. There was significant improvement in plant height, number of flowers and bolls formed, boll weight and seed cotton yield in most of the treatments as compared to uninoculated control. Synergistic effects of dual inoculation of all the A. chroococcum strains with AM fungi were observed for boll weight and seed cotton yield. A significant positive correlation between population of Azotobacter sp. in rhizosphere of cotton with weight of bolls and seed cotton yield was observed.